Social Identities of Young Indigenous People in Contemporary Australia: Neo-colonial North, Yarrabah - Jang, Hae Seong (Springer, 2015)
This volume is about the social identities of young Indigenous people in contemporary Australia, based on fieldwork in the rural community of Yarrabah, in Queensland. This case study of Yarrabah is based on seventeen ethnographic interviews with women and men in their twenties. With the aim of exploring how diverse social discourses have influenced the social identities of young Indigenous people in contemporary Australia, this book represents the life histories of these young people in Yarrabah in the context of both the institutions with which they interact and the everyday shape of life in Yarrabah. This volume also provides new material for discussion of the ways in which Indigenous value systems, broadly understood by the participants to be based on collectivism, constantly come into conflict with Western values based on individualism. While the young Indigenous people of Yarrabah do continuously interact not only with multi‑cultural Australia but also with global influences, they are constantly aware of their own distinctiveness in both contexts.